Customer Experience And Satisfaction: The Impact Of Augmented Reality In Online Shopping - Michelle Alicia Lynch; William Leo Walangitan; Aaron Kennedy; Hari Setiabudi Husni (Asosiasi Dosen Muda Indonesia, 2025)
The rapid growth of e-commerce presents challenges related to limited product visualization and customer engagement, which refers to the degree to which customers feel actively involved in the online shopping experience. Augmented Reality (AR) technology has the potential to offer an innovative solution by providing an immersive shopping experience that makes customers feel as if they are interacting directly with products through virtual simulations. This research aims to explore how AR can provide a deeper customer experience and satisfaction in online shopping, such as realistically visualizing products before purchase, with an example application of the